2007
DOI: 10.1002/ijc.22739
|View full text |Cite
|
Sign up to set email alerts
|

Increased health care utilization among long‐term cancer survivors compared to the average Dutch population: A population‐based study

Abstract: In the present study, self-reported health care utilization of cancer survivors is compared with those of an age-and gender-matched normative population and predictors of health care utilization are identified. A population-based, cross-sectional survey among 1893 long-term survivors of endometrial and prostate cancer and malignant lymphomas (Hodgkin's and non-Hodgkin's) diagnosed between 1989 and 1998 was conducted using the cancer registry of the Comprehensive Cancer Centre South. Cancer survivors visited th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…These same results were also found in another article based on this database. 39 However, in that particular study, we did not make a difference for age groups. A difference in survivors under and above the age of 75 was made in a Dutch study among 10-year breast cancer survivors and the results confirm our findings.…”
Section: Pf Rp Re Vt Mh Sf Bp Gh Pcs Mcs Pf Rp Re Vt Mh Sf Bp Gh Pcs mentioning
confidence: 69%
“…These same results were also found in another article based on this database. 39 However, in that particular study, we did not make a difference for age groups. A difference in survivors under and above the age of 75 was made in a Dutch study among 10-year breast cancer survivors and the results confirm our findings.…”
Section: Pf Rp Re Vt Mh Sf Bp Gh Pcs Mcs Pf Rp Re Vt Mh Sf Bp Gh Pcs mentioning
confidence: 69%
“…There were no significant differences in use of specialist services such as mental health. Some studies have found that cancer survivors had greater use of GP services [30,22] and medical specialists; other studies have presented mixed evidence [31].…”
Section: Predictors Of Health and Wellbeingmentioning
confidence: 99%
“…2,3 Moreover, owing to the generally good prognosis of 80% 5-year survival, there is a large and growing group of endometrial cancer survivors. 3 Survivors show an increased specialist care use even long after the end of treatment, 4,5 whereas for primary care use, results are more diverse. Some studies report an increased primary care use among cancer survivors compared to the general population, 6,7 whereas others could not confirm this, possibly owing to small samples.…”
mentioning
confidence: 99%
“…Some studies report an increased primary care use among cancer survivors compared to the general population, 6,7 whereas others could not confirm this, possibly owing to small samples. 4,5,8 Health care use differs by cancer type; and therefore, a specific description for endometrial cancer is needed.…”
mentioning
confidence: 99%
See 1 more Smart Citation